Enriched HLA-E and CD94/NKG2A interaction limits antitumor CD8+ tumor-infiltrating T lymphocyte responses - Abd Hamid, M; Wang, R; Yao, X; Fan, P; Li, X; Chang, X; Feng, Y; Jones, S; Maldonado-Perez, D; Waugh, C; Verrill, C; Simmons, A; et al. (American Association for Cancer Research, 2019)
Immunotherapy treatments with anti-PD-1 boost recovery in less than 30% of treated cancer patients, indicating the complexity of the tumor microenvironment. Expression of HLA-E is linked to poor clinical outcomes in mice and human patients. However, the contributions to immune evasion of HLA-E, a ligand for the inhibitory CD94/NKG2A receptor, when expressed on tumors, compared with adjacent tissue and peripheral blood mononuclear cells, remains unclear. In this study, we report that epithelial-derived cancer cells, tumor macrophages, and CD141+ conventional dendritic cells (cDC) contributed to HLA-E enrichment in carcinomas. Different cancer types showed a similar pattern of enrichment. Enrichment correlated to NKG2A upregulation on CD8+ tumor-infiltrating T lymphocytes (TIL) but not on CD4+ TILs. CD94/NKG2A is exclusively expressed on PD-1high TILs while lacking intratumoral CD103 expression. We also found that the presence of CD94/NKG2A on human tumor–specific T cells impairs IL2 receptor–dependent proliferation, which affects IFNγ-mediated responses and antitumor cytotoxicity. These functionalities recover following antibody-mediated blockade in vitro and ex vivo. Our results suggest that enriched HLA-E:CD94/NKG2A inhibitory interaction can impair survival of PD-1high TILs in the tumor microenvironment.